Composite Carbon Nanotube Microsphere Coatings for Use as Electrode Supports. (27th September 2018) - Fraser, Alison; Zhang, Zishuai; Merle, Geraldine; Gbureck, Uwe; Ye, Siyu; Gostick, Jeff; Barralet, Jake
Abstract: Carbon nanotubes and titania, highly corrosion‐resistant materials, are successfully assembled into high surface area microparticles (162 m 2 g −1 ) in one step using low‐power ultrasound. The composite microparticles are electrically conductive (>0.4 S cm −1 ). The microparticles are deposited as an electrical layer (<2.5 µm) on a stainless‐steel mesh gas diffusion layer using a tribochemical coating technique. Long‐term durability testing in 0.5m H2 SO4 at 80 °C confirms the corrosion resistance of the catalyst coating. This coating method may have wider applicability for other electrical and electrochemical devices that require thin corrosion‐resistant coatings. Abstract : A thin catalyst layer is deposited on a stainless‐steel mesh gas diffusion layer via a tribochemical coating technique using composite titanium dioxide and carbon nanotube microparticles as a precursor. The resulting coating is catalytically active and highly corrosion resistant. This coating technique may have further applicability for other electrical applications.